Kesiapan Belajar Siswa Pada Pembelajaran Tatap Muka Mata Pelajaran IPA Terpadu - Yulianto; Hadma Yuliani; Nur Inayah Syar (Lembaga Bale Literasi, 2022)
Abstract - The topic of this research was purposed to understanding the readiness of students to receive a face-by-face learning at integrated science lesson. This study took the research methond in the form of descriptive qualitative. This topic was conducted at SMP IT Sahabat Alam Palangka Raya with 10 students of class 2 junior high school as a reaserch subjects. The data gathering technique by the researcher is a questionnaire. The research data were analyzed descriptively with reference to the ability category scale. By the results of the research that has been analyzed, that can be concluded the level of student learning readiness in face-by-face learning at integrated science subjects is on range “very good” criteria. Abstrak - Topik penelitian ini diangkat dengan intensi untuk memahami kesiapan anak didik dalam menerima pembelajaran secara tatap muka pada pelajaran IPA Terpadu. Penelitian ini mengambil metode penelitian berupa kualitatif deskriptif. Penelitian dilaksanakan di SMP IT Sahabat Alam Palangka Raya dengan subjek penyelidikan sebanyak 10 anak didik kelas VIII. Teknik pengambilan data yang dipakai peneliti adalah angket/ kuesioner. Data hasil penelitian dianalisis secara deskriptif dengan acuan skala kategori kemampuan. Dari hasil penelitian yang telah dianalisis bisa ditarik kesimpulan bahwa tingkat kesiapan belajar siswa dalam pembelajaran tatap muka pada mata pelajaran IPA Terpadu termasuk pada kriteria “sangat baik”.